A study of the potential of adult mesenchymal stem cells in bone and cartilage tissue engineering - Farrell, Eric (Trinity College (Dublin, Ireland). Department of Physiology, 2006)
Adult mesenchymal stem cells (MSCs) have the potential to self-renew and differentiate into bone, cartilage, fat and muscle cells. This cell population offers significant potential for engineering of musculoskeletal tissue. The aim of my PhD was to generate viable bone and cartilage constructs from MSCs. Successful tissue engineering requires a suitable 3-dimensional (3-D) environment, which was provided by a novel collagen glycosaminoglycan (Collagen-GAG) scaffold. Bone and cartilage formation from adult MSCs seeded onto collagen GAG scaffolds was induced and some of the intracellular signalling mechanisms behind this process were characterised. My work optimised the techniques required to culture MSCs for an extended period of time and verified the presence of MSCs in culture and their proliferation capacity. My first study examined the potential for MSCs to be directed along the osteogenic pathway in a 2-D environment. To that end, cells were treated with osteoinductive factors for three weeks. This led to significant osteocalcin expression, a late stage protein marker of osteogenesis. The induction of osteocalcin was abolished by the inhibition of ERK using the selective inhibitor U0126, suggestive of a role for ERK in osteogenesis. Also, a timecourse study showed that ERK activity was induced at day 10 of treatment with osteoinductive factors. Activity of p38, was shown to be upregulated at day 7.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin